2020
DOI: 10.1093/nar/gkaa540
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the dimeric RappLS20 anti-repressor of the conjugation operon is mediated by peptide-induced tetramerization

Abstract: Quorum sensing allows bacterial cells to communicate through the release of soluble signaling molecules into the surrounding medium. It plays a pivotal role in controlling bacterial conjugation in Gram-positive cells, a process that has tremendous impact on health. Intracellular regulatory proteins of the RRNPP family are common targets of these signaling molecules. The RRNPP family of gene regulators bind signaling molecules at their C-terminal domain (CTD), but have highly divergent functionalities at their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 50 publications
(81 reference statements)
1
14
0
Order By: Relevance
“…disruption of these complexes and the appearance of elution and SAXS patterns that were similar to those of Rco pLS20 alone and Rap pLS20 -Phr* pLS20 complexes (i.e., Rap pLS20 tetramers) (Crespo et al, 2020).…”
Section: The Activation State Of the Conjugation Genes Is Ultimately mentioning
confidence: 75%
See 4 more Smart Citations
“…disruption of these complexes and the appearance of elution and SAXS patterns that were similar to those of Rco pLS20 alone and Rap pLS20 -Phr* pLS20 complexes (i.e., Rap pLS20 tetramers) (Crespo et al, 2020).…”
Section: The Activation State Of the Conjugation Genes Is Ultimately mentioning
confidence: 75%
“…Instead, Rap pLS20 seems to exert its antirepressor activity by binding directly to Rco pLS20 , as bacterial two-hybrid analysis showed that Rap pLS20 and Rco pLS20 interact in vivo ( Singh et al, 2020 ). In vitro evidence that Rap pLS20 interacts directly with Rco pLS20 has also been obtained by SAXS and analytical size exclusion chromatography ( Crespo et al, 2020 ). Furthermore, AUC analyses provided conclusive evidence that Rap pLS20 forms predominantly dimers in solution.…”
Section: Rap Pls20 Activates Conjugation By Detachmentioning
confidence: 96%
See 3 more Smart Citations